Squid Ink Polysaccharides Protect Human Fibroblast Against Oxidative Stress by Regulating NADPH Oxidase and Connexin43 - Chen, Ying; Liu, Huazhong; Huang, Hao; Ma, Yuetang; Wang, Ruihua; Hu, Yong; Zheng, Xiufen; Chen, Chunmei; Tang, Hongfeng (Frontiers in Pharmacology, 2020)
Oxidation injury to skin is one of the main reasons for skin aging. The aim of the present study was to explore the protective effect of squid ink polysaccharide and its mechanism of action against H2O2-induced dermal fibroblast damage. Our results show that squid ink polysaccharides effectively reduce the fibroblast oxidative damage mediated by the up-regulation of NADPH oxidase and Connexin43. Concurrently, squid ink polysaccharides decrease the ROS induced the up-regulation of MMP1 and MMP9 to decrease MMP-mediated skin aging. Therefore, we hypothesized that squid ink polysaccharide overcomes the inhibition of NADPH oxidase and Connexin43 the expression to exert its antioxidant effect. This provides a new target for the effective clinical prevention and treatment of oxidative skin damage.